High-efficiency photoelectrochemical cathodic protection performance of the iron-nitrogen-sulfur-doped TiO2 nanotube as new efficient photoanodes - Mohamad Mohsen Momeni; Mohammad Taghinejad; Yousef Ghayeb; Robabeh Bagheri; Zhenlun Song (Materials Research Express, 2020)
Novel iron-nitrogen-sulfur-tridoped titanium dioxide nanotubes (Fe-N-S-TiO _2 NTs) have been synthesized via single step anodization of titanium using potassium ferricyanide, as a suitable additive, in dimethyl sulfoxide (DMSO) electrolyte and applied as photoanodes in the photocathodic protection of stainless steel 403 (SS403). Photocurrent density, open circuit potential and Tafel polarization curves have been used to study the photocathodic protection effect of the samples prepared. Upon the addition of potassium ferricyanide to the anodizing electrolyte and titanium dioxide nanotube doping, the light absorption of the Fe-N-S-TiO _2 NTs were increased to the visible region, comparable with pure TiO _2 NTs, according to the results obtained. Enhanced photoelectro-response activity and photocathodic protection performance for 403 stainless steel are exhibited by Fe-N-S-TiO _2 NTs under light illumination. In addition, the optimal sample electrode (FT4) potentials shifted negatively to −683 mV under illumination.